Automodel Solutions of Biberman-Holstein Equation for Stark Broadening of Spectral Lines - Alexander B. Kukushkin; Vladislav S. Neverov; Petr A. Sdvizhenskii; Vladimir V. Voloshinov (Atoms, 2018)
The accuracy of approximate automodel solutions for the Green’s function of the Biberman-Holstein equation for the Stark broadening of spectral lines is analyzed using the distributed computing. The high accuracy of automodel solutions in a wide range of parameters of the problem is shown.